Convective Rainfall Z-R Equation Characteristics for C-Band Weather Radar in the Jakarta Region - Muhammad Fadhillah; Yosafat Donni Haryanto; Purwanti Lelly Sabrina; Dodo Gunawan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Operational quantitative precipitation estimation (QPE) from the C-Band weather radar in Jakarta still relies on the generic Marshall-Palmer (Z=200R^1.6) and Rosenfeld Tropical (Z=250R^1.2) Z-R relationships, neither calibrated to the local Drop Size Distribution (DSD) of convective rainfall in this tropical maritime region. This study aimed to derive a locally modified Z-R coefficient specific to convective rain, defined as rain rate ≥10 mm/hour, using a statistical regression optimization approach. Volumetric raw data (.vol) from the Tangerang C-Band radar were paired with hourly rainfall records from 32 automatic rain gauges (ARG and AWS) within a 50 km radius during January–April 2024, following Column Maximum (CMAX) extraction and quality control procedures. Linear regression on log-transformed reflectivity and rainfall data yielded a new convective equation, Z=152R^1.4, with a correlation coefficient of 0.6972 and coefficient of determination of 0.4861. These moderate values are consistent with the naturally wide Drop Size Distribution spectrum of convective rainfall, rather than indicating a weak physical relationship between reflectivity and rain rate. Taylor Diagram verification showed the new equation sustaining a correlation of approximately 0.95, close to observed variability, with root mean square error near 3.9 dBZ, outperforming Marshall-Palmer and Rosenfeld Tropical in balancing correlation and standard deviation under convective conditions. These findings support operational adoption of a locally derived convective Z-R relationship for Jakarta's radar-based rainfall estimation.